2015
DOI: 10.1186/s40104-015-0056-6
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value of high fiber co-products from the copra, palm kernel, and rice industries in diets fed to pigs

Abstract: High fiber co-products from the copra and palm kernel industries are by-products of the production of coconut oil and palm kernel oil. The co-products include copra meal, copra expellers, palm kernel meal, and palm kernel expellers. All 4 ingredients are very high in fiber and the energy value is relatively low when fed to pigs. The protein concentration is between 14 and 22 % and the protein has a low biological value and a very high Arg:Lys ratio. Digestibility of most amino acids is less than in soybean mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
61
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 49 publications
11
61
3
3
Order By: Relevance
“…The chemical composition of WB (Jaworski, Lærke, Bach Knudsen, & Stein, ; Jaworski et al, ; Zhao, Zhang, Xie, Li, & Huang, ), SBP (Lyu, Huang, Li, Li, Liu, et al, ), CGF (Jaworski et al, ), SBH (Lyu, Huang, Li, Li, Liu, et al, ; Stewart et al, ), and DFRB (Lyu, Li, Liu, et al, ; Stein, Casas, Abelilla, Liu, & Sulabo, ) showed great variabilities due to different origin, species, and processing technology. Take CGF for example, the nutrients composition of CGF depends largely on processing technology which mix different fractions of corn therefore producing different corn coproducts (Jaworski et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The chemical composition of WB (Jaworski, Lærke, Bach Knudsen, & Stein, ; Jaworski et al, ; Zhao, Zhang, Xie, Li, & Huang, ), SBP (Lyu, Huang, Li, Li, Liu, et al, ), CGF (Jaworski et al, ), SBH (Lyu, Huang, Li, Li, Liu, et al, ; Stewart et al, ), and DFRB (Lyu, Li, Liu, et al, ; Stein, Casas, Abelilla, Liu, & Sulabo, ) showed great variabilities due to different origin, species, and processing technology. Take CGF for example, the nutrients composition of CGF depends largely on processing technology which mix different fractions of corn therefore producing different corn coproducts (Jaworski et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The palm kernel product was classified as the expellers because the concentration of ether extract in the feed ingredient was 6.97% [6]. …”
Section: Methodsmentioning
confidence: 99%
“…Mechanical extraction by screw pressing is the most common process in oil extraction from palm kernels, which results in production of palm kernel expellers (PKE; Sulabo, Ju, & Stein, ). The PKE has a concentration of ether extract (EE) of 4 to 8% (Alimon, ) and is primarily produced in Southeast Asia, Africa, and Latin America (Stein, Casas, Abelilla, Liu, & Sulabo, ). These by‐products have gained increasing attention in pig production (Stein, Lagos, & Casas, ).…”
Section: Introductionmentioning
confidence: 99%